The role of taking into account the interatomic interaction in predicting the complex of structurally-sensitive properties of steels and alloys for special purpose - Snihura, I.R.; Togobitskaya, D.N. (Фундаментальные и прикладные проблемы черной металлургии, 2018)
The aim of the work is to identify the influence of the chemical composition of steels and special-purpose alloys on the formation of their physicochemical and structural-sensitive properties. This problem is solved by mathematical modeling of the inseparable chain «composition - structure – property» taking into account the parameters of interatomic interaction in the melt based on the concept of a directed chemical bond. Целью работы является выявление влияния химического состава сталей и сплавов специального назначения на формирование их физико-химических и структурно-чувствительных свойств. Эта задача решается путем математического моделирования неразделимой цепочки «состав - структура - свойство» с учетом параметров межатомного взаимодействия в расплаве на основе концепции направленной химической связи. Метою роботи є виявлення впливу хімічного складу сталей і сплавів спеціального призначення на формування їх фізико-хімічних і структурно-чутливих властивостей. Це завдання вирішується шляхом математичного моделювання нероздільного ланцюжка «склад - структура - властивість» з урахуванням параметрів міжатомної взаємодії в розплаві на основі концепції спрямованої хімічного зв'язку.